Penerapan Model Tipe Kancing Gemerincing Untuk Meningkatkan Penguasaan Konsep Siswa Materi Sumber Daya Alam - Dianti Risharni (Institut Pendidikan Indonesia, 2019)
Abstract - This research is motivated by the low level of mastery of the science concept of students in SDNegeri Jagakarsa 02 Pagi, South Jakarta. The low level of mastery of students' concepts is because the teacherin teaching in the class still adheres to the old paradigm of using the lecture method. This can be seen at thebeginning of the study by giving practice questions about the topic of natural resources, the results showedthat the average of all students has not reached the target mastery of the desired concept. Some indicators ofthe concept of the questions given still have not reached the level of mastery. Based on these problems, theremust be an effort to improve the mastery of the science concept of students in grade IV SD Negeri Jagakarsa02 Pagi, South Jakarta. Therefore, the efforts made by researchers on